Donaldsonian Themes: A Commentary. Issue 1 (28th November 2016) - Donaldson, Thomas
ABSTRACT: The articles in the special issue of Business Ethics Quarterly (2015), "Normative Business Ethics in a Global Economy: New Directions on Donaldsonian Themes, " were written by a set of outstanding scholars: Margaret M. Blair, Joseph P. Gaspar, Nien-hê Hsieh, Peter L. Jennings, Marietta Peytcheva, Andreas Georg Scherer, Amy J. Sepinwall, Andrew Stark, Danielle E. Warren, and Manuel Velasquez. In this commentary I reply to my colleagues, arranging my reply around the following themes: 1) the corporate moral agent; 2) the idea of a social contract for business; 3) managing ethics within corporations; and 4) values in business. I discuss each in turn. However, I reflect first on my idiosyncratic approach to business ethics.